In vitro and in vivo anthelmintic activity of (-)-6,6 '-dinitrohinokinin against schistosomula and juvenile and adult worms of Schistosoma mansoni - Pereira, Ana C.; Silva, Marcio L. A. e; Souza, Julia Medeiros; Laurentiz, Rosangela S. de [UNESP]; Rodrigues, Vanderlei; Januario, Ana H.; Pauletti, Patricia M.; Tavares, Denise C.; Da Silva Filho, Ademar A.; Cunha, Wilson R.; Bastos, Jairo K.; Magalhaes, Lizandra G. (Elsevier B.V., 2015)
The chemotherapy of schistosomiasis relies on the use of praziquantel. However, concerns over drug resistance have encouraged the search for new drug leads. This paper is the first report on the in vitro and in vivo activity of (-)-6,6'-dinitrohinokinin (DNK) against Schistosoma mansoni. In vitro, the lethal concentrations for 50% of parasites (LC50) of DNK against adult worms were 103.9 +/- 3.6 and 102.5 +/- 4.8 mu M at 24 and 72 h, respectively. Scanning electron microscopy images showed extensive tegumental alterations such as peeling and smaller numbers of tubercles in the spine of adult worms. DNK also elicited high mortality of schistosomula, with LC50 values of 57.4 +/- 2.3, 32.5 +/- 0.9, and 20.4 +/- 1.2 mu M at 24, 48, and 72 h, respectively. DNK displayed moderate activity against the juvenile liver parasite, with an LC50 value of 179.5 +/- 2.3 mu M at 72 h. This compound reduced the total number of eggs by over 83%, and it affected the development of eggs produced by adult worms. The selectivity index showed that at 24 h, DNK was 8.5 and 15.4 times more toxic to the adult worms and schistosomula than to Chinese hamster lung fibroblast cells, respectively. Treatment of infected mice with DNK moderately decreased worm burden (33.8-52.3%), egg production (40.7-60.0%), and spleen and liver weights. Together, our results indicated that DNK presents moderate in vitro and in vivo activities against S. mansoni, and it might therefore be interesting to explore the structure-activity relationship of the antischistosomal activity of this compound. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Lignan; (-)-6,6 '-Dinitrohinokinin; Schistosoma mansoni